A Versatile Precursor System for Supercritical Fluid Electrodeposition of Main‐Group Materials. Issue 1 (26th November 2015) - Bartlett, Philip N.; Burt, Jennifer; Cook, David A.; Cummings, Charles Y.; George, Michael W.; Hector, Andrew L.; Hasan, Mahboba M.; Ke, Jie; Levason, William; Pugh, David; Reid, Gillian; Richardson, Peter W.; et al.
Abstract: For the first time, a versatile electrolyte bath is described that can be used to electrodeposit a wide range of p‐block elements from supercritical difluoromethane (scCH2 F2 ). The bath comprises the tetrabutylammonium chlorometallate complex of the element in an electrolyte of 50×10 −3  mol dm −3 tetrabutylammonium chloride at 17.2 MPa and 358 K. Through the use of anionic ([GaCl4 ] −, [InCl4 ] −, [GeCl3 ] −, [SnCl3 ] −, [SbCl4 ] −, and [BiCl4 ] − ) and dianionic ([SeCl6 ] 2− and [TeCl6 ] 2− ) chlorometallate salts, the deposition of elemental Ga, In, Ge, Sn, Sb, Bi, Se, and Te is demonstrated. In all cases, with the exception of gallium, which is a liquid under the deposition conditions, the resulting deposits are characterised by SEM, energy‐dispersive X‐ray analysis, XRD and Raman spectroscopy. An advantage of this electrolyte system is that the reagents are all crystalline solids, reasonably easy to handle and not highly water or oxygen sensitive. The results presented herein significantly broaden the range of materials accessible by electrodeposition from supercritical fluid and open up the future possibility of utilising the full scope of these unique fluids to electrodeposit functional binary or ternary alloys and compounds of these elements. Abstract : Compatible conditions : The electrodeposition of a range of p‐block elements under compatible conditions from supercritical difluoromethane opens up the possibility of electrodepositing sub‐20 nm nanostructures of a wide range of p‐block binary and ternary alloys and compounds (see figure).